Phytochemical Investigation and in vitro Evaluation of Anthelmintic Activity of Gmnelina arborea roxb. Fruit Extracts - Shankar Nayak, Bhabani; Kumar Jena, Prabhat; Chandra Dinda, Subas; Ellaiah, P. (Asian Journal of Chemistry, 2012)
Zmelina arborea Roxb. is found in the tribal areas of Koraput and Ganjam district of Odisha, India. It is extensively used traditionally by the tribal people as anthelmintic, antimicrobial, antifungal, antidiabetic and hepatoprotective. The present study is an attempt for the preliminary investigation of phytochemical constituents and to explore the anthelmintic activity of different extracts of unripe fruits of plant Z. arborea using ethanol, ethyl acetate, n-butanol and petroleum ether as solvents. The extracts were screened for phytochemical constituents and evaluated for their anthelmintic activity on adult Indian earthworms, Pheretima posthuma. The tests for cardiac glycosides and steroids were positive for all the extracts. The ethanol and n-butanol extracts were containing most phytochemicals where as ethyl acetate extracts was containing least number of phytochemicals. All extracts were able to show anthelmintic activity at 10 mg/ mL concentration. The activities are comparable with the standard drugs such as piperazine citrate and albendazole. All the doses of ethanol, ethyl acetate and petroleum ether extracts of Z. arborea showed lesser anthelmintic activity than the standard drugs piperazine citrate and albendazole except ethanol extract at 25 mg/mL of concentration which showed better anthelmintic activity than the both standard drugs. When the dose of such extract is increased, a gradual increase in anthelmintic activity was observed. Among all the solvent extracts the n-butanol extract showed better anthelmintic activity even in comparison with both the standard drugs. The data were verified as statistically significant by using one way ANOVA at 5 % level of significance (p < 0.05).